PENDIDIKAN AGAMA KATOLIK SEBAGAI MEDIA KOMUNIKASI IMAN BAGI REMAJA DI STASI SANTO FRANSISKUS BENANGIN - Nurbeta Nurbeta; Silvester Adinuhgra; Fransiskus Janu Hamu; Widya Ariyani (Sepakat : Jurnal Pastoral Kateketik, 2019)
The purpose of this thesis is to depart from the problems faced by Catholic adolescents, relating to the number of teenagers not active in activities in the Church, and falling into promiscuity. Departing from this issue, the need for the role of Catholic Religious Education to transfer the values of Faith to Catholic youth. Thesis entitled "Catholic Religion Education as a Media of Faith Communication for Youth in Saint Francis Benagin" aims to provide correct understanding to Catholic youth about the importance of Catholic Religion Education as a medium to translate Catholic Faith values so that Catholic youth can become adolescents with integrity , productive, competitive, innovative and has a good spirituality life. The method used in this research is qualitative method. Data obtained by observation, interviews and documentation. Research steps include, conversations with informants, informant profiles, reflection, synthesis, prospects or possibilities that will occur.